(untitled) (Razi Medical Journal, 2025)
Intestinal obstruction, whether acute or chronic, is a common surgical condition, particularly among elderly patients. Acute obstruction, however, is more prevalent in younger and middle-aged adults. Multiple etiologies contribute to this condition, and different therapeutic strategies can be employed. This retrospective study aimed to evaluate the effectiveness of early surgical intervention compared to conservative management in selected cases. Conducted at Misurata Central Hospital and private clinics between June 2016 and July 2019, the study included 34 adult and pediatric patients with acute intestinal obstruction. All patients presented with at least one symptom, including abdominal pain, distension, vomiting, constipation, or complete obstipation, and occasionally anorexia or lethargy. Diagnosis was primarily based on clinical evaluation and upright abdominal radiographs; CT scans were used selectively. Early surgery was performed in 22 patients, while 12 initially received conservative treatment. Five of the latter group required surgery due to clinical deterioration, revealing near-ischemic or gangrenous bowel. The findings indicate that early surgery is as safe as conservative therapy and offers the advantage of reducing bowel resection and related morbidity. Careful clinical evaluation supported by appropriate investigations is essential to prevent severe complications, including bowel ischemia and gangrene.